Ответы и объяснения

2014-04-13T12:38:11+04:00
1)2-2(3х-4)=-2
  2-6х+8=-2
  -6х=-2-8-2
  -6х=-12
  х=-12:(-6)
  х=2
2) -5+9х=10х+4
   9х-10х=4+5
   -х=9
   х=9:(-1)
   х=-9
3) -8+7(-х-2)=6 
   -8-7х-14=6
   -7х=6+14+8
   -7х=28
    х=28:(-7)
   х=-4
4) 9(х-5)=-х
  9х-45=-х
  9х+х=45
  10х=45
   х=45:10
   х=4,5
5) 9(х-6)=4х
   9х-54=4х
  9х-4х=54
  5х=54
  х=54:5
  х=10,8
6) 10(х+4)=9х
  10х+40=9х
  10х-9х=-40
   х=-40
7) 4(х-7)=3х
  4х-28=3х
  4х-3х=28
  х=28
8) 3(х-8)=5х
   3х-24=5х
  3х-5х=24
  -2х=24
  х=24:(-2)
  х=-12